2023
DOI: 10.1021/acs.est.2c07255
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors Are Associated with the Abundance of PFAS Sources and Detection in U.S. Community Water Systems

Abstract: Drinking water contaminated by per- and polyfluoroalkyl substances (PFAS) is a widespread public health concern, and exposure–response relationships are known to vary across sociodemographic groups. However, research on disparities in drinking water PFAS exposures and the siting of PFAS sources in marginalized communities is limited. Here, we use monitoring data from 7873 U.S. community water systems (CWS) in 18 states to show that PFAS detection is positively associated with the number of PFAS sources and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…For presumptive contamination sites and known PFAS users (described below), our analysis does not differentiate based on magnitude of potential or likely contamination. Consistent with prior studies identifying PFAS contaminated sites, ,, our goal is to identify point locations where PFAS have likely been used and/or released, thus leading to concerns about likely contamination.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…For presumptive contamination sites and known PFAS users (described below), our analysis does not differentiate based on magnitude of potential or likely contamination. Consistent with prior studies identifying PFAS contaminated sites, ,, our goal is to identify point locations where PFAS have likely been used and/or released, thus leading to concerns about likely contamination.…”
Section: Methodsmentioning
confidence: 93%
“…We used the OurAirports online database to identify all commercial civilian airports in the EU . Following expert advice from ECHA, we excluded small airports and heliports and selected only large and medium airports as well as 102 closed airports with an asphalted runway.…”
Section: Methodsmentioning
confidence: 99%
“…While no differences were found between redlined and nonredlined neighborhoods for certain environmental hazards, disparities may still exist. For instance, within the United States, racial–ethnic disparities for air pollution, , chemical toxins, and water quality still persist. Within California, recent research has shown that racially marginalized communities throughout California continue to face disproportionate exposure to oil and gas wells and the associated disturbances, higher levels of water contamination, and lower reductions in PM 2.5 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, disparities in the siting of these sources make it more likely that public drinking water supplies serving communities with higher proportions of Hispanic/Latino and non-Hispanic Black residents are contaminated with PFAS. 4 It is estimated that 200 million people in the United States rely on tap water contaminated with PFAS, 5 and >2000 communities in 49 states have PFAS concentrations in municipal drinking water that exceeds levels of concern. 6 In response, the National Academies of Sciences, Engineering and Medicine (NASEM) convened a committee to develop principles for testing PFAS concentrations in people living in 7 There are significant exposure sources in addition to drinking water.…”
mentioning
confidence: 99%